A Comprehensive Assessment of Knowledge, Self-reported Practices and Barriers Regarding Personal Hygiene among 1st Year Bachelor Students of Baneshwor Multiple Campus (BMC), Kathmandu, Nepal, 2023 - Ghimire, Labanya Devi; Lamichhane, Shamila; Lamichhane, Samir (Baneshwor Campus Journal of Academia, 2025)
Background: Personal hygiene is strongly influenced by an individual’s knowledge and practices towards hygiene, as well as social, cultural, familial, and behavioral barriers related to it. Maintaining good personal hygiene is important to limit the spread of infectious diseases and minimize the absenteeism of students in colleges and universities. The objective of this research is to evaluate the knowledge, self-reported practices, and perceived barriers to personal hygiene among first-year bachelor’s students at Baneshwor Multiple Campus, Kathmandu, Nepal. The study employed a descriptive cross-sectional design and used a self-administered, semi-structured questionnaire to collect data from 216 first-year bachelor-level students. The descriptive statistics used in the study for data analysis includes frequency, percentage, mean and standard deviation. The study participants’ mean age was 19.43 years with a standard deviation of 2.13. 46.3% of study participants were male and 53.7% were females. The majority of students (87.4%) were found to have good level of knowledge on personal hygiene, with females having higher scores than males. Nearly half of students (49.07%) were found to have a good level of self-reported practices on personal hygiene, with females having slightly higher scores than males. Laziness was expressed as the top barrier (64.81%) to personal hygiene, followed by lack of time (63.89%), lack of materials (62.5%), lack of water supply (60.65%), customs/beliefs (60.65%), and lack of information-education (52.78%). Nearly 2/3rd (63.43%) reported that the campus has good facilities for personal hygiene, whereas nearly four-fifths replied of never received a personal hygiene session at campus (73.61%) and the materials provided by campus were inadequate (74.54%) respectively.